2008
DOI: 10.1002/sia.2845
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the bond‐making and bond‐breaking of Fe‐filled SWNT on Ni(111)

Abstract: aIn the previous studies, the stable structures and magnetic properties of Fe-filled single-walled carbon nanotubes (SWNTs) on Ni (111) were investigated based on first principles calculations. The SWNT transformed into arch-like structure when the Fe atom was placed inside it near the Ni surface.In order to fully understand the formation of nanoarch when placed near the metal surface, we have provided a detailed mechanism of the bond-breaking of SWNT and the bond-making of SWNT-Fe and Ni surface.The electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They can also be decorated and modified to tailor to specific applications: i.e. metal-filled SWCNTs with modified electronic and magnetic properties [8][9][10][11][12][13]. Hydrogen fuel cells have been the subject of interest in the search for alternative sources of energy.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be decorated and modified to tailor to specific applications: i.e. metal-filled SWCNTs with modified electronic and magnetic properties [8][9][10][11][12][13]. Hydrogen fuel cells have been the subject of interest in the search for alternative sources of energy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Experimentally, titanium has been found to be a potentially viable electrode because it demonstrates uniform distribution and has a strong interaction with SWNTs. Recently, several researches are focused on the device applications of SWNT.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, a simple ultrasonic nanowelding technique has been developed to bond SWNT onto Ti electrodes and found that the bonds formed between the two have been demonstrated to be mechanically robust and have a stable low-Ohmic contact at room temperature. [2][3][4][5][6] The Fe nanowire and the metal surface served as catalysts in transforming the sp 2 characteristic of C atom near the surface and Fe atom into sp 3 hybrid orbitals. Theoretically, Meng et al reported that there is no potential barrier between Ti surface and ͑10, 0͒ semiconducting SWNT and they strongly bind chemically.…”
Section: Introductionmentioning
confidence: 99%